2020
DOI: 10.1002/mds.28412
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Obstructive Sleep Apnea on Cognitive and Motor Functions in Parkinson's Disease

Abstract: A BS TRACT: Introduction: Parkinson's disease (PD) is a chronic neurodegenerative disorder that presents with motor and non-motor manifestations. Amongst the nonmotor features, various forms of sleep disturbances can occur, and obstructive sleep apnea (OSA) is considered to be a common comorbidity. We conducted this systematic review and meta-analysis to assess the impact of OSA on cognitive and motor functions in PD. Methods: The information sources of for this systematic review and meta-analysis were PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 67 publications
0
31
0
Order By: Relevance
“…Sleep disturbances are commonly associated with neurodegenerative diseases and are known to greatly affect the quality of life of patients [ 119 ]. For example, sleep disorders, such as nighttime insomnia, daytime hypersomnia, and rapid eye movement (REM) sleep disorders, are often seen in patients with AD [ 159 , 188 ] or PD [ 77 , 253 ]. Many effective sedative-hypnotic drug products, including benzodiazepine and Z-drugs (e.g., zolpidem, zaleplon, zopiclone) are used to induce and/or maintain sleep in people with sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances are commonly associated with neurodegenerative diseases and are known to greatly affect the quality of life of patients [ 119 ]. For example, sleep disorders, such as nighttime insomnia, daytime hypersomnia, and rapid eye movement (REM) sleep disorders, are often seen in patients with AD [ 159 , 188 ] or PD [ 77 , 253 ]. Many effective sedative-hypnotic drug products, including benzodiazepine and Z-drugs (e.g., zolpidem, zaleplon, zopiclone) are used to induce and/or maintain sleep in people with sleep disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia is associated with impairments in cognitive performance, and thus, relieving insomnia could potentially improve cognitive outcome [24]. A recent systematic review and meta-analysis showed that obstructive sleep apnea was associated with signi cantly lower MoCA scores in patients with PD [25]. Increased sleep fragmentation and nocturnal hypoxia are important mechanisms, contributing to impair cognition [22].…”
Section: Discussionmentioning
confidence: 99%
“…We extracted the following domains using an offline data extraction sheet [ 23 ]: (1) last name of first author, (2) year of publication, (3) design, (4) population characteristics, (5) sample size, (6) accessible data of studied outcomes, and (7) risk of bias.…”
Section: Methodsmentioning
confidence: 99%